'Me estoy labrando tu sombra': la posesión de la amada en La voz a ti debida, de Pedro Salinas. - LARIOS, JORDI (Hispanic Research Journal, 2010)
In the late 1980s C. Christopher Soufas claimed that critics had studied the poetry of the so-called 'Generación del 27' without reference to its historical context or the artistic and philosophical debates that took place in Europe as well as in Spain during the first quarter of the twentieth century. Bearing in mind the point made by Soufas, the aim of this article is to suggest an interpretation of La voz a ti debida (1933) which differs from the existing ones in that it places Salinas's poem firmly within the framework of one of the most important philosophical debates that took place in Europe in the first quarter of the last century: the debate on the life-culture or life-reason dichotomy, to which Ortega made an outstanding contribution.